2015
DOI: 10.1371/journal.pbio.1002247
|View full text |Cite
|
Sign up to set email alerts
|

The Maternal Maverick/GDF15-like TGF-β Ligand Panda Directs Dorsal-Ventral Axis Formation by Restricting Nodal Expression in the Sea Urchin Embryo

Abstract: Specification of the dorsal-ventral axis in the highly regulative sea urchin embryo critically relies on the zygotic expression of nodal, but whether maternal factors provide the initial spatial cue to orient this axis is not known. Although redox gradients have been proposed to entrain the dorsal-ventral axis by acting upstream of nodal, manipulating the activity of redox gradients only has modest consequences, suggesting that other factors are responsible for orienting nodal expression and defining the dorsa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
110
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(126 citation statements)
references
References 76 publications
15
110
1
Order By: Relevance
“…In a recent paper [40], the partial or complete protein sequences of five hbox12/pmar1/micro1 family members were inferred from one contig of P . lividus genomic sequence.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent paper [40], the partial or complete protein sequences of five hbox12/pmar1/micro1 family members were inferred from one contig of P . lividus genomic sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Analogously, pairwise alignments showed that the proteins predicted for the hbox12-02 , - 04 and - 27 genes displayed the highest similarity to the three remaining sequences, although various differences were detected (S2 Fig). Although these discrepancies could be at least in part due to allelic polymorphisms, in the absence of genomic sequence for the contig described in [40], we cannot rule out the possibility that we were looking at further distinct copies of the same gene family, which probably escaped from the sequencing and/or assembly of the P . lividus genomic reads.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, prioritizing these features can also yield to choices of model organisms that display some developmental similarities to each other, but are not representative of the larger taxa to which they belong. Furthermore, some cnidarians and echinoderms use induction for PGC specification (1) and yet certain data have suggested that maternal products deposited in the egg (products of the Frizzled protein family that activate Wnt signaling in cnidarians and Panda gene products in echinoderms) may partly contribute toward directing embryonic body plans in these groups, raising the possibility that the mechanism of PGC formation and axial patterning are uncoupled in some organisms (64,65). Together, further investigations of mechanisms of embryonic axis formation and PGCspecification modes across a wider range of metazoans will be needed to decipher whether a shift toward use of maternal determinants for embryonic patterning typically cooccurs with germ plasm, consistent with a spandrel effect.…”
Section: Evolution Of Inheritance May Not Necessarily Depend On Its Ementioning
confidence: 99%